2020
DOI: 10.1016/j.esg.2020.100073
|View full text |Cite
|
Sign up to set email alerts
|

Delaying decarbonization: Climate governmentalities and sociotechnical strategies from Copenhagen to Paris

Abstract: An era (2005–2015) centered around the Copenhagen Accord saw the rise of several immature sociotechnical strategies currently at play: carbon capture and storage, REDD+, next-generation biofuels, shale gas, short-lived climate pollutants, carbon dioxide removal, and solar radiation management. Through a framework grounded in governmentality studies, we point out common trends in how this seemingly disparate range of strategies is emerging, evolving, and taking effect. We find that recent sociotechnical strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 106 publications
(171 reference statements)
0
26
0
3
Order By: Relevance
“…A wider body of research on CE assesses how different types of discourse may be shaping the development of technology governance (Harnisch et al, 2015;Biermann and Möller, 2019;Boettcher, 2019;Low and Boettcher, 2020;Möller, 2020). This research has demonstrated how discussions on the feasibility and responsibility of various CE approaches have prioritized scientific and technical knowledge types Barben, 2018, 2020;Low and Schäfer, 2020).…”
Section: The Role Of Discoursementioning
confidence: 99%
“…A wider body of research on CE assesses how different types of discourse may be shaping the development of technology governance (Harnisch et al, 2015;Biermann and Möller, 2019;Boettcher, 2019;Low and Boettcher, 2020;Möller, 2020). This research has demonstrated how discussions on the feasibility and responsibility of various CE approaches have prioritized scientific and technical knowledge types Barben, 2018, 2020;Low and Schäfer, 2020).…”
Section: The Role Of Discoursementioning
confidence: 99%
“…These governance meta-discourses, in turn, can be tied to a longer arc of liberal and neoliberal governmentalities outlined by historical Foucauldian analyses of western democracies (Foucault, 2008;Kerchner, 2010;Kerchner and Schneider, 2010). Governing logics which have historically underpinned climate and carbon governance (and western democratic governance per se) are therefore seemingly being reproduced within NETs governance discourse, highlighting the persistent shaping function of existing power/knowledge structures on the emergence of new objects, subjects and instruments of governance (Carton et al, 2020;Low and Boettcher, 2020;McLaren and Markusson, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…My analysis has shown that these three discursive blueprints for systems of thinking about the nature of NETs governance may also be present in wider discussions of NETs policy instruments, and be further reproducing elements of green governmentality, ecological modernization and civic environmentalism which have historically shaped wider climate governance. This raises the question as to whether NETs governance may end up being shaped by the same power/knowledge structures that have been criticized for producing climate governance arrangements which delay the decarbonization of the global economy, and how this could be circumvented (Low and Boettcher, 2020;McLaren and Markusson, 2020).…”
Section: Conclusion: Coming To Grips With the Shaping Effects Of Discmentioning
confidence: 99%
See 1 more Smart Citation
“…Why does BECCS matter? BECCS, and through it, the prospect of large-scale tCDR, emerged at the confluence of key trends in climate assessment and governance: it is an immature technological system that allows ambitious temperature targets to be reached in IPCC mitigation pathways, while reflecting rationales for "buying time" in climate policy and industry (Low and Boettcher, 2020;McLaren and Markusson, 2020). These trends are escalating how terrestrial environments have been made thinkable and practicable as operating spaces for CDR, and reinforcing the legitimacy of CDR as a response to climate change.…”
Section: Is Blue the New Green?mentioning
confidence: 99%